2007
DOI: 10.1196/annals.1397.005
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cells Response to the Antineoplastic Agents Cisplatin, Carboplatin, and Doxorubicin at the mRNA Expression Levels of Distinct Apoptosis‐Related Genes, Including the New Member, BCL2L12

Abstract: Most apoptosis-related genes regulate cellular fate as a response to anticancer drugs. Modulations at the mRNA levels of such genes often correlate with the sensitivity of various types of cancer cells to chemotherapeutic reagents. The drugs cisplatin, carboplatin, and doxorubicin exhibit anticancer activity, the mechanism of which is not yet completely clarified, although they are known to modulate the expression of several genes including apoptosis-related genes, such as members of the BCL2 (Bcl-2) family. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
(34 reference statements)
1
28
0
6
Order By: Relevance
“…In an earlier study from our lab, the usage of cisplatin, a second generation platinum analog, led to exactly the opposite fluctuations in BCL2L12 transcript levels at two time points (24 and 48 h). 53 Moreover, the response of MCF-7 33,54 and MDA-MB-231 33 to cisplatin generated comparable results with ours with respect to the expression of this gene. The time-dependent (up to 24 h) enhanced transcriptional activity of BCL2L12 upon incubation of MDA-MB-231 with cisplatin in conjunction with the overexpression of the corresponding protein promoted apoptosis induced by this particular drug.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In an earlier study from our lab, the usage of cisplatin, a second generation platinum analog, led to exactly the opposite fluctuations in BCL2L12 transcript levels at two time points (24 and 48 h). 53 Moreover, the response of MCF-7 33,54 and MDA-MB-231 33 to cisplatin generated comparable results with ours with respect to the expression of this gene. The time-dependent (up to 24 h) enhanced transcriptional activity of BCL2L12 upon incubation of MDA-MB-231 with cisplatin in conjunction with the overexpression of the corresponding protein promoted apoptosis induced by this particular drug.…”
Section: Discussionsupporting
confidence: 83%
“…56 BAX profiles were unaffected, as a result of OVCAR-3 and BT-20 cancer cells' response to carboplatin, cisplatin or doxorubicin addition, or they became under-expressed in doxorubicin-treated MCF-7 breast carcinoma cells. 54,55 Such discrepancies could be explained on the context of concrete features of the cellular systems examined as well as by the discrete pathways that are induced as a consequence of the cytotoxic action of every different chemotherapeutic agent utilized. An overview of the BCL-2 alterations that is in general line with recent literature, [53][54][55] included drastic (in methotrexate treatment) or great (for doxorubicin or oxaliplatin-treated AGS cells) reductions in its mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, overexpression of one or more of the GAS5 ESTs induced or facilitated apoptosis in all the cell lines examined. In the mouse thymoma W7.2c and the breast epithelial MCF-10A cell lines, overexpression of GAS5 did not induce growth arrest by itself, but did produce a clear increase in sensitivity to treatments that induce apoptosis by several different pathways (Fan et al, 1995;Lam et al, 1997;Rossini et al, 2001; Mourtada-Maarabouni et al, 2003a; Thomadaki and Scorilas, 2007). For the breast epithelial MCF-7 and HEK 293T cell lines, overexpression of some GAS5 ESTs induced apoptosis without any additional stimulus (Figures 4b and 5a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we previously reported that expression of BCL2L12-A, an alternative transcript of BCL2L12, appears to be of importance in colon cancer, since it is associated with Dukes' stage and lymph node status (49). Remarkable modulations of BCL2L12 mRNA levels have also been observed in HL-60 (50-54) and SHI-1 (55) leukemia cells, MCF7 breast adenocarcinoma cells (56,57), OVCAR-3 ovary adenocarcinoma cells (58), AGS (59) and SGC7901 (60) gastric cancer cells, after treatment with various antineoplastic agents. These important alterations in BCL2L12 expression seem to depend on the apoptotic pathway that is triggered by each apoptotic inducer, implying a strong relationship between changes in BCL2L12 mRNA levels and apoptosis.…”
Section: Discussionmentioning
confidence: 96%